DUST FALL RATE AND ITS COMPOSITION IN CHANDRAPUR INDUSTRIAL CLUSTER, CENTRAL INDIA - Kamble, R. K. (International Journal of Environment, 2015)
Dust is one of the significant air pollutants in ambient air of Chandrapur industrial cluster. A study was carried out to ascertain the dust fall rate in four sampling locations in the Chandrapur industrial cluster of Chandrapur district, central India. The sampling was carried out by dust fall jar method in winter season (2014-2015) and dust fall rate was estimated gravimetrically. Maximum dust fall rate was recorded in Nakoda 246.67 MT sq km-1 month-1 (industrial area, downwind direction), followed by CSTPS colony 171.77 MT sq km-1 month-1 (industrial area, downwind direction) whereas minimum concentration was found in Babupeath 55.54 MT sq km-1 month-1 (residential area, downwind direction) for December-January. Whereas, during sampling period of February-March maximum dust fall rate was observed to be 278.14 MT sq km-1 month-1 at Babupeath (residential area, upwind direction) and minimum dust fall rate was observed at Ballarpur 173.74 MT sq km-1 month-1 (industrial, upwind direction). The results indicated that dust fall rate for the sampling period of December-January in industrial cluster region was higher as compared with residential region. It has been also observed that upwind direction sampling locations had lesser dust fall rate as compared with downwind direction. The composition of dust fall from study area was dominated by water soluble components. Water insoluble components were comprised of inorganic insoluble and volatile matter. Total inorganic component per cent by weight was maximum in dust. International Journal of Environment Volume-4, Issue-3, June-August 2015 Page: 96-110